Speed breeding opportunities and challenges for crop improvement - Sharma, Shivani; Kumar, Amit; Dhakte, Priyanka; Raturi, Gaurav; Vishwakarma, Gautam; Barbadikar, Kalyani M.; Das, B. K.; Shivaraj, S. M.; Sonah, Humira; Deshmukh, Rupesh (Journal of Plant Growth Regulation, 2023)
Crop improvement in light of the rapidly changing climate and the increasing human population continues to be one of the primary concerns for researchers across the globe. The rate at which current crop improvement programs are progressing is essentially inadequate to meet the food demand. There is an urgent need for redesigning the crops for climate resilience and sustainable yield and nutrition. The rate of crop improvement is largely impeded owing to the long generation time taken by crop plants during the breeding process. As a solution in this direction, speed breeding is now being practiced at a large scale to reduce generation time to accommodate multiple generations of crops per year. To enhance the efficiency of breeding, researchers are now adopting an integrated approach where speed breeding is used along with modern plant breeding and genetic engineering technologies. In the present review, we have summarized the technological aspects, opportunities, and limitations associated with speed breeding. The application of speed breeding such as mapping population development, haplotype-based breeding, transgenic breeding, and genome-edited line advancement has also been discussed. Speed breeding is a promising technology that expedites the goals of food and industrial crop improvement by reducing the breeding cycles for establishing nutritional security and sustainable agriculture.
Keywords: Genome editing; Genomic selection; Haplotype breeding; Speed breeding; Transgenic breeding